Knowledge and attitudes on human papillomavirus (HPV) infection and HPV vaccination among health clinic nurses in the state of Kelantan - Kandeepan, Jeyachelvi (2016)
INTRODUCTION: Cervical cancer, though preventable, is still the leading cause of cancer death among women in Malaysia second to breast cancer. Persistent infection with HPV has been causally linked to cervical cancer. The school-based HPV vaccination program was introduced in late 2010. Nurses’ support is imperative for the success of this program; however, it has not been assessed yet. This study aims to determine factors associated with their knowledge score. METHODS: A survey was conducted from June till July 2014 at health clinics in Kelantan. The nurses were selected through the multistage random sampling process, and selfadministered questionnaires were distributed to 352 nurses. Data were analyzed using SPSS version 22. Multiple linear regression models were used to determine the variables associated with the nurses’ knowledge score. RESULTS: A total of 330 completed questionnaires were analyzed and showed that: 32.4% nurses participated from the outpatient unit and 67.6% from maternal and child health unit. The mean knowledge score (SD) was 5.3 (1.7) out of 11. Only, 24% knew that HPV is the most common sexually transmitted virus; 67% knew that Gardasil protects against four types of HPV and 29% correctly answered the target age of vaccination. Nursing qualification (p<0.001) was the only factor that significantly associated with knowledge score. HPVrelated work experience, having children in vaccination age group and reading resources showed no influence in knowledge score. CONCLUSION: This is the first study done in Kelantan to assess nurses’ knowledge in this regard. Findings from this study indicate nurses have favorable attitudes toward HPV vaccination, but they are in urgent need of improving HPV- related knowledge and its actual vaccination. Similar studies need to be conducted in other states, to have a broad estimation and to make a nationally based education program to increase nurses’ knowledge in this matter.